The kynurenine pathway metabolites in cord blood positively correlate with early childhood adiposity - Tan, Karen Mei-Ling (2022)
Context: The kynurenine pathway generates metabolites integral to energy metabolism, neurotransmission, and immune function. Circulating kynurenine metabolites positively correlate with adiposity in children and adults, yet it is not known whether this relationship is present already at birth. Objective: In this prospective longitudinal study, we investigate the relationship between cord blood kynurenine metabolites and measures of adiposity from birth to 4.5 years. Methods: Liquid chromatography–tandem mass spectrometry was used to quantify cord blood kynurenine metabolites in 812 neonates from the Growing Up in Singapore Towards healthy Outcomes (GUSTO) study. Fat percentage was measured by air displacement plethysmography and abdominal adipose tissue compartment volumes; superficial (sSAT) and deep subcutaneous (dSAT) and internal adipose tissue were quantified by magnetic resonance imaging at early infancy in a smaller subset of neonates, and again at 4 to 4.5 years of age. Results: Cord blood kynurenine metabolites appeared to be higher in female newborns, higher in Indian newborns compared with Chinese newborns, and higher in infants born by cesarean section compared with vaginal delivery. Kynurenine, xanthurenic acid, and quinolinic acid were positively associated with birthweight, but not with subsequent weight during infancy and childhood. Quinolinic acid was positively associated with sSAT at birth. Kynurenic acid and quinolinic acid were positively associated with fat percentage at 4 years. Conclusion: Several cord blood kynurenine metabolite concentrations were positively associated with birthweight, with higher kynurenic acid and quinolinic acid correlating to higher percentage body fat in childhood, suggesting these cord blood metabolites as biomarkers of early childhood adiposity.